5th International Conference on Higher Education Advances (HEAd'19) 2019
DOI: 10.4995/head19.2019.9131
|View full text |Cite
|
Sign up to set email alerts
|

Students’ experiences with the use of a social annotation tool to improve learning in flipped classrooms

Abstract: To support the development and dissemination of more activating educational practices, pilot studies were launched on the use of the social annotation tool Perusall. During 2016-2017 several  managers of higher education course units worked with Perusall in classes of a size varying from 10 to more than hundred students. To assess the usefulness and effectiveness of Perusall we focused on two related aspects (1) perception by students of Perusall as an appropriate tool to support the processing of the study te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 2 publications
2
31
0
Order By: Relevance
“…Similarly, there seems to be limited research that explores the use of Perusall for psychology students. Most research results collected from students refers to natural sciences or engineering subjects (e.g., Lee & Yeong, 2018;Lepek & Coppens, 2016;Lepek & Radl, 2019;Liberatore, 2017;Pejcinovic, 2018), rather than from a social science perspective (e.g., Suhre et al, 2019;Sun & Smith, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, there seems to be limited research that explores the use of Perusall for psychology students. Most research results collected from students refers to natural sciences or engineering subjects (e.g., Lee & Yeong, 2018;Lepek & Coppens, 2016;Lepek & Radl, 2019;Liberatore, 2017;Pejcinovic, 2018), rather than from a social science perspective (e.g., Suhre et al, 2019;Sun & Smith, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Also, as regards students' perceptions or opinions about the automated assessment process, there seem to be no studies. There are some studies that analysed the perceptions, reactions, and critiques relating, more generally, to Perusall, for instance, the students' experience using Perusall; or investigated aspects related to learning (e.g., Liberatore, 2017;Suhre, Winnips, de Boer, Valdivia, & Beldhuis, 2019;Sun & Smith, 2019).…”
Section: Study Validity Of Automated Scoringmentioning
confidence: 99%
“…Across the three chosen courses, a total of thirty-three of the fifty-nine students enrolled in the courses (56%) responded to the survey (Table 1). Surveys are an appropriate method for analyzing embedded units within a single-case study (Yin, 2018) and, as previously reviewed, are a common method among studies that examine student perceptions of SA (e.g., Chen, 2019;Gao, 2013;Suhre et al, 2019).…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…Not included in the Novak et al (2012) review were confirmatory findings by Su et al (2010, p. 764), who compared student perceptions of SA to more conventional discussion forums. Results from a survey of 45 undergraduate students studying computer science found favorable attitudes about the perceived usefulness, ease of use and learning satisfaction of a SA tool; specifically, “most of the students thought that group learning scenarios with annotation systems did increase their interest, happiness and achievements in collaborative learning.” Alternatively, Suhre et al (2019, p. 960) also studied university students’ perceptions of SA ease of use and found – despite no reported sample size from students in eight courses, and little detail about how the survey was designed – that student perceptions were negatively influenced by “reading from a computer screen and expressed disconcern [sic] about the obligatory number of annotations.”…”
Section: Literature Reviewmentioning
confidence: 99%
“…Perusall is a collaborative annotation system that allows students and instructors to add comments and questions to documents, images, and videos [1]. Past research has indicated that completing Perusall assignments can contribute to deep learning for students [2], and, among engineering graduate students, led to more self-reported learning [3]. The system has been often illustrated as a tool for pre-reading assignments in a flipped classroom [4], however it can also be used for completely asynchronous components of a course, whether online or in-person.…”
Section: Introductionmentioning
confidence: 99%